WESTERN COLONIZATION AND POLITICAL RESISTANCE IN THE ISLAMIC WORLD: A HISTORICAL STUDY OF THE INDEPENDENCE STRUGGLES OF MUSLIM COUNTRIES - Fatmal, Abd. Bashir; Rizkayadi; Nurhayati; Syukur, Syamzan; Rahmawati (Jurnal Diskursus Islam, 2025)
Western colonization of the Islamic world from the 16th century to the mid-20th century is a historical phenomenon that had a profound impact on the socio-political, economic and cultural order of Muslims. This study aims to critically examine the dynamics of Western colonization and the various forms of political resistance that emerged in the Islamic world as a response to colonial domination. Using a historical-comparative approach, this study traces the diverse patterns of struggle, ranging from armed jihad, elite diplomacy, to social and intellectual movements that later shaped national consciousness and religious identity in various Islamic regions. The study reveals that the struggle for independence of Muslim countries was not only a political effort against foreign rule, but also a process of reconstructing cultural and religious identities that played an important role in the formation of post-colonial nation-states. The study also highlights how the legacy of these struggles has strategic relevance in facing the challenges of neocolonialism, political fragmentation and foreign intervention in the contemporary era. In addition, this study affirms the importance of the role of Muslims in building the future of civilization that is inclusive, sustainable, and based on Islamic spiritual and social values. The findings are expected to provide a comprehensive conceptual and historical contribution in understanding the relationship between colonialism, political resistance and religious identity in the Islamic world.